A composite carrier catalyst and its preparation method and application
By using the preparation method of composite support catalyst, the problem of easy deactivation of the catalyst at high temperature is solved by using components such as aluminum hydroxide, Y-type molecular sieve and divalent copper salt, and the effect of high catalytic activity and long life is achieved.
Patent Information
- Application Number
- CN202410814403.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-06-24
AI Technical Summary
Existing catalysts are prone to deactivation at high temperatures, resulting in a decrease in catalytic activity and it is difficult to meet the needs of high stability and high catalytic activity.
By using the preparation method of a composite support catalyst, a composite support catalyst with high catalytic activity and stability is formed by mixing, drying, and calculating components such as aluminum hydroxide, Y-type molecular sieve and divalent copper salt.
The high catalytic activity and long life of the catalyst were achieved, and the hydrogen chloride conversion rate remained at a high level after 8h and 1000h, the reaction activity temperature decreased, and the yield increased.
Smart Images

Figure CN118744010B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a composite carrier catalyst and a preparation method and application thereof. Background Art
[0002] With the large-scale expansion of chlorine-related products and the development of the chlor-alkali industry, the disposal and utilization of a large amount of by-product HCl has become a common problem that restricts the environment and the development of many industries. At the same time, the demand for chlorine products is increasing, and the supply and demand relationship of chlorine is becoming increasingly tense. If the by-product hydrogen chloride is converted into chlorine, it will alleviate the contradiction of the imbalance between the supply and demand of chlorine, and fundamentally eliminate the environmental pollution caused by the by-product hydrogen chloride while improving economic benefits.
[0003] At present, the method of preparing chlorine from hydrogen chloride has attracted more and more attention due to its relatively easy application and low energy consumption. The catalysts studied in the catalytic oxidation method are mainly copper-based catalysts, which produce chlorine by oxidizing hydrogen chloride with oxygen. They have excellent activity, low cost and easy regeneration, but due to the high reaction temperature, the catalyst is easily deactivated. Therefore, many scholars have done a lot of work in its preparation method, matching of active metals, properties of carriers, reactor structure and process conditions, aiming to improve the catalyst life and reaction activity.
[0004] Chinese patent CN114713250A discloses using activated alumina as a carrier and CuF as an active component. 2 or CuCl 2 On the basis of, the catalytic active component CuClF was added to obtain a catalyst. 2g of the catalyst was added to a fixed bed reactor, in a molar ratio of hydrogen chloride and oxygen of 2:1, the hydrogen chloride feed flow rate was 16mL / min, the reaction temperature was 370℃, and the reaction pressure was 0.1MPa. The measured hydrogen chloride conversion rate was 90.2%, and the hydrogen chloride conversion rate after 20h of reaction was 89.5%. The life of the catalyst was slightly reduced after 20h of use, indicating good stability, but excellent catalytic activity was not shown by simply changing the active component.
[0005] Therefore, how to further improve the catalytic activity of the catalyst while ensuring high stability has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a composite carrier catalyst and a preparation method and application thereof. The composite carrier catalyst prepared by the preparation method provided by the present invention has high catalytic activity and high stability.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a composite supported catalyst, comprising the following steps:
[0009] (1) mixing aluminum hydroxide, Y-type molecular sieve and a first solvent, and sequentially drying and first calcining to obtain a composite carrier;
[0010] (2) mixing the composite carrier obtained in step (1), the divalent copper salt and the second solvent, and performing loading to obtain a carrier loaded with the precursor;
[0011] (3) The carrier loaded with the precursor obtained in step (2) is subjected to a second calcination to obtain a composite carrier catalyst.
[0012] Preferably, the Y-type molecular sieve in step (1) comprises a mesoporous Y-type molecular sieve and / or a microporous Y-type molecular sieve.
[0013] Preferably, the temperature of the first calcination in step (1) is 480-580° C., and the time of the first calcination is 3-4 hours.
[0014] Preferably, in step (1), the γ-Al 2 O 3 The mass content is 50-90%.
[0015] Preferably, in step (2), the mass ratio of the divalent copper salt to the composite carrier is (0.4-0.5):1.
[0016] Preferably, the loading temperature in step (2) is room temperature, and the loading time is 10 to 12 hours.
[0017] Preferably, the temperature of the second calcination in step (3) is 430-580° C., and the time of the second calcination is 4-5 hours.
[0018] Preferably, the step (2) further comprises adding a trivalent cerium salt.
[0019] The present invention also provides a composite carrier catalyst prepared by the preparation method described in the above technical solution.
[0020] The present invention also provides the use of the composite carrier catalyst described in the above technical solution in the catalytic oxidation of hydrogen chloride to produce chlorine.
[0021] The present invention provides a method for preparing a composite carrier catalyst, comprising the following steps: mixing aluminum hydroxide, Y-type molecular sieve and a first solvent, and sequentially drying and first calcining to obtain a composite carrier; mixing the composite carrier, a divalent copper salt and a second solvent, and loading to obtain a carrier loaded with a precursor; and second calcining the carrier loaded with a precursor to obtain a composite carrier catalyst. The present invention improves the carrier by mixing the Y-type molecular sieve and γ-Al2 O 3 The composite is used as a carrier, and the acidic center of the Y-type molecular sieve and the γ-Al 2 O 3 The catalytic activity and selectivity of the catalyst are improved under the joint action of the acidic sites of the catalyst; the composite of the carrier can optimize the pore structure of the single carrier, improve the adsorption performance and diffusion performance of the catalyst, and thus improve the catalytic activity on the basis of ensuring the stability of the catalyst; the present invention is used in the preparation of γ-Al 2 O 3 Adding Y-type molecular sieve during the process can grow γ-Al with smaller particle size around the Y-type molecular sieve. 2 O 3 The particles are further increased in specific surface area of the catalyst, thereby further increasing the catalytic activity. The experimental results show that the chlorine yield of the catalyst prepared by the present invention when catalyzing hydrogen chloride to produce chlorine is 90.6-97.6% after 8 hours of reaction, and 89.8-97.2% after 1000 hours of reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a process flow chart of the composite supported catalyst provided by the present invention. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing a composite supported catalyst, comprising the following steps:
[0024] (1) mixing aluminum hydroxide, Y-type molecular sieve and a first solvent, and sequentially drying and first calcining to obtain a composite carrier;
[0025] (2) mixing the composite carrier obtained in step (1), the divalent copper salt and the second solvent, and performing loading to obtain a carrier loaded with the precursor;
[0026] (3) The carrier loaded with the precursor obtained in step (2) is subjected to a second calcination to obtain a composite carrier catalyst.
[0027] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0028] In the present invention, the first and the second have no special meanings and are only used to distinguish the steps.
[0029] The present invention mixes aluminum hydroxide, Y-type molecular sieve and a first solvent, and sequentially performs drying and a first calcination to obtain a composite carrier. 2 O 3 In the process of adding Y-type molecular sieve, γ-Al with smaller particle size will grow around the Y-type molecular sieve. 2 O3 Particles, compared to direct mixing, the specific surface area of the catalyst is larger.
[0030] In the present invention, the preparation method of aluminum hydroxide preferably comprises the following steps:
[0031] 1) mixing aluminum hydroxide, sodium hydroxide and a solvent, and performing a first neutralization reaction to obtain a sodium aluminate solution;
[0032] 2) mixing the sodium aluminate solution obtained in step 1) with an acidic solution, and performing a second neutralization reaction to obtain aluminum hydroxide gel;
[0033] 3) The aluminum hydroxide gel obtained in step 2) is mixed with ammonia water to perform a precipitation reaction to obtain aluminum hydroxide. The present invention adopts the above preparation process to prepare aluminum hydroxide of the desired crystalline form, thereby facilitating the preparation of γ-Al 2 O 3 .
[0034] In the present invention, aluminum hydroxide, sodium hydroxide and a solvent are preferably mixed to carry out a first neutralization reaction to obtain a sodium aluminate solution.
[0035] In the present invention, the solvent is preferably an inorganic solvent, more preferably deionized water. The present invention has no particular limitation on the amount of the solvent, as long as the raw materials can be dissolved.
[0036] In the present invention, the mass ratio of the aluminum hydroxide to the sodium hydroxide is preferably 1:1.
[0037] The present invention has no particular limitation on the operation of mixing the aluminum hydroxide, sodium hydroxide and the solvent, and the operation well known to those skilled in the art may be adopted.
[0038] In the present invention, the time of the first neutralization reaction is preferably 1 to 3 hours. The present invention has no particular limitation on the temperature of the first neutralization reaction, as long as the reaction solution is boiled.
[0039] In the present invention, the first neutralization reaction is preferably carried out under stirring conditions. The present invention has no particular limitation on the stirring operation, and any operation well known to those skilled in the art may be used.
[0040] After the first neutralization reaction is completed, the present invention preferably cools and filters the product obtained by the first neutralization reaction in sequence to obtain a sodium aluminate solution.
[0041] The present invention has no special limitation on the cooling operation, and cooling to room temperature can be performed by a cooling operation well known to those skilled in the art. The present invention has no special limitation on the suction filtration operation, and operations well known to those skilled in the art can be performed. The present invention can remove a small amount of undissolved aluminum hydroxide by suction filtration.
[0042] After obtaining the sodium aluminate solution, the present invention preferably mixes the sodium aluminate solution with an acidic solution to perform a second neutralization reaction to obtain aluminum hydroxide gel.
[0043] In the present invention, the acidic solution is preferably a nitric acid solution. The present invention has no particular limitation on the concentration and dosage of the nitric acid solution, as long as the pH value of the reaction solution is adjusted to within the range of 7.5 to 8.5.
[0044] In the present invention, the second neutralization reaction is preferably carried out under stirring conditions. The present invention has no particular limitation on the stirring operation, and any operation well known to those skilled in the art may be used.
[0045] In the present invention, the temperature of the second neutralization reaction is preferably 40 to 50° C.; the time of the second neutralization reaction is preferably 0.5 to 1 h.
[0046] After the second neutralization reaction is completed, the present invention preferably filters the product obtained from the second neutralization reaction to obtain aluminum hydroxide gel.
[0047] The present invention has no particular limitation on the filtration operation, and any operation well known to those skilled in the art may be used.
[0048] After obtaining the aluminum hydroxide gel, the present invention preferably mixes the aluminum hydroxide gel with ammonia water to perform a precipitation reaction to obtain aluminum hydroxide.
[0049] The present invention has no particular limitation on the concentration and dosage of the aqueous ammonia, and the pH value of the reaction solution can be controlled at 8.0.
[0050] The present invention has no special limitation on the operation of mixing the aluminum hydroxide gel and ammonia water, and a technical scheme for preparing a mixed material well known to those skilled in the art is adopted.
[0051] In the present invention, the temperature of the precipitation reaction is preferably 40-45°C; the precipitation reaction is preferably carried out under stirring conditions. The present invention has no special limitation on the stirring operation, and the operation well known to those skilled in the art can be adopted. The present invention has no special limitation on the time of the precipitation reaction, and the time can be until no precipitation is regenerated.
[0052] After the precipitation reaction is completed, the present invention preferably sequentially filters and washes the product obtained by the precipitation reaction to obtain aluminum hydroxide.
[0053] The present invention has no particular limitation on the filtration and washing operations, and operations well known to those skilled in the art may be used.
[0054] In the present invention, the Y-type molecular sieve preferably includes a mesoporous Y-type molecular sieve and / or a microporous Y-type molecular sieve. When the Y-type molecular sieve is a mesoporous Y-type molecular sieve and a microporous Y-type molecular sieve, the present invention has no particular limitation on the ratio of the two.
[0055] In the present invention, the first solvent is preferably an inorganic solvent, more preferably deionized water. The present invention has no particular limitation on the amount of the first solvent, as long as the raw materials are dissolved.
[0056] The present invention has no special limitation on the operation of mixing the aluminum hydroxide, the Y-type molecular sieve and the first solvent, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.
[0057] After the mixing is completed, the present invention preferably ages the mixed product.
[0058] In the present invention, the aging temperature is preferably room temperature; the aging time is preferably 10 to 12 hours. The aging method of the present invention is helpful to obtain aluminum hydroxide with a purer, more uniform particle size and more stable crystal form.
[0059] The present invention has no special limitation on the drying operation, and the operation well known to those skilled in the art can be adopted. The present invention adopts drying to remove the solvent.
[0060] In the present invention, the temperature of the first calcination is preferably 480-580°C, more preferably 500-580°C; the time of the first calcination is preferably 3-4 hours. The present invention can form γ-Al by controlling the temperature and time of the first calcination. 2 O 3 .
[0061] In the present invention, the first calcination is preferably performed in an air atmosphere.
[0062] In the present invention, the γ-Al 2 O 3 The mass content of γ-Al in the composite carrier is preferably 50-90%. 2 O 3 The mass content of γ-Al in the composite carrier can be adjusted 2 O 3 and Y-type molecular sieve, thereby further improving the catalytic activity and stability of the catalyst.
[0063] After obtaining the composite carrier, the present invention mixes the composite carrier, the divalent copper salt and the second solvent for loading to obtain the carrier loaded with the precursor.
[0064] In the present invention, the divalent copper salt is preferably copper nitrate; the second solvent is preferably an inorganic solvent, more preferably deionized water.
[0065] In the present invention, the mass ratio of the divalent copper salt to the composite carrier is preferably (0.4-0.5):1, more preferably 0.453:1; the mass ratio of the divalent copper salt to the volume of the second solvent is preferably (0.1-0.5) g:1 mL, further preferably (0.2-0.3) g:1 mL, more preferably 0.2265 g:1 mL. The present invention can further improve the loading effect by controlling the mass ratio of the divalent copper salt to the composite carrier, thereby improving the activity and stability of the catalyst.
[0066] In the present invention, the mixing of the composite carrier, the divalent copper salt and the second solvent is preferably performed by mixing the divalent copper salt with the second solvent and then adding the composite carrier.
[0067] The present invention has no particular limitation on the mixing operation, and any operation well known to those skilled in the art may be used.
[0068] In the present invention, the preparation of the carrier loaded with the precursor preferably further includes adding a trivalent cerium salt; the trivalent cerium salt is preferably a nitrate. The present invention can further improve the activity and selectivity of the catalyst by adding a trivalent cerium salt as an auxiliary agent, thereby promoting the catalytic reaction.
[0069] In the present invention, the trivalent cerium salt is preferably mixed with the divalent copper salt and the second solvent at the same time; the mass ratio of the trivalent cerium salt to the second solvent is preferably (0.1-0.5) g:10 mL, more preferably (0.2-0.3) g:10 mL, and more preferably 0.23 g:10 mL. The present invention can further improve the activity and stability of the catalyst by controlling the ratio of the two.
[0070] In the present invention, the loading temperature is preferably room temperature; the loading time is preferably 10 to 12 hours. The present invention can further improve the loading effect by controlling the loading temperature and time, thereby improving the activity and stability of the catalyst.
[0071] In the present invention, the loading is preferably performed under static conditions.
[0072] After the loading is completed, the present invention preferably dries and grinds the loaded product to obtain a carrier loaded with the precursor.
[0073] The present invention has no particular limitation on the drying and grinding operations, and operations well known to those skilled in the art may be used.
[0074] After obtaining the carrier loaded with the precursor, the present invention performs a second calcination on the carrier loaded with the precursor to obtain a composite carrier catalyst.
[0075] In the present invention, the temperature of the second calcination is preferably 430-580°C, more preferably 450-500°C; the time of the second calcination is preferably 4-5 hours; the second calcination is preferably carried out in an air atmosphere. The present invention can further improve the calcination effect by controlling the calcination temperature and time, thereby improving the activity and stability of the catalyst.
[0076] The present invention combines microporous Y-type molecular sieve and / or mesoporous Y-type molecular sieve with γ-Al 2 O 3 After mixing, the active substance copper nitrate is loaded to obtain a composite dual-carrier catalyst which can greatly improve the catalytic ability and service life of the catalyst. The composite dual-carrier catalyst has strong catalytic activity and a low optimal activity temperature.
[0077] The composite carrier catalyst prepared by the present invention is γ-Al 2 O 3 and Y-type molecular sieve as composite carrier (γ-Al with smaller particle size) 2 O 3 Highly dispersed around the Y-type molecular sieve), Cu 2+ As the active component, Ce is added 3+ As an auxiliary agent, the composite carrier catalyst has the advantages of long service life, good high temperature stability, high catalytic activity, etc. The use of the composite carrier catalyst for catalytic oxidation of hydrogen chloride to produce chlorine can not only improve the efficiency of preparing chlorine from hydrogen chloride, but also reduce the optimal active temperature of the reaction and extend the life of the catalyst. At the same time, the optimal reaction activity temperature dropped by 40°C and the yield increased by 10%.
[0078] The process flow chart of the composite supported catalyst provided by the present invention is as follows Figure 1 shown.
[0079] from Figure 1 It can be seen that the present invention first reacts sodium hydroxide and aluminum hydroxide, adjusts the pH value after cooling and filtering, then heats, stirs and filters, then adds ammonia water, filters and washes, adds molecular sieves, adds active components for impregnation after standing, drying and calcining, and then stands and then sequentially dries, grinds and calcines to prepare a composite carrier catalyst.
[0080] The present invention also provides a composite carrier catalyst prepared by the preparation method described in the above technical solution.
[0081] In the present invention, the composite supported catalyst preferably comprises a composite support and an active component supported on the composite support;
[0082] The composite carrier is preferably a Y-type molecular sieve and γ-Al 2 O 3 ; The active component preferably includes copper oxide.
[0083] In the present invention, the active component preferably also includes Ce 2 O 3 .
[0084] In the present invention, the Y-type molecular sieve and γ-Al 2 O 3 The mass ratio of CuO to Ce in the active component is preferably 1:(1-5), more preferably 1:(1-2); 2 O 3 The mass ratio is preferably (10-15):1.
[0085] The composite carrier catalyst provided by the invention has high catalytic activity and high stability.
[0086] The present invention also provides the use of the composite carrier catalyst described in the above technical solution in the catalytic oxidation of hydrogen chloride to produce chlorine.
[0087] In the present invention, the application operation of the composite supported catalyst in the catalytic oxidation of hydrogen chloride to produce chlorine is preferably:
[0088] 1. Molding the composite carrier catalyst to obtain a molded catalyst;
[0089] 2. The molded catalyst obtained in step 1 is used to catalyze oxidation reaction of hydrogen chloride in an oxygen atmosphere to obtain chlorine.
[0090] In the present invention, the composite carrier catalyst is preferably shaped to obtain a shaped catalyst.
[0091] In a technical solution of the present invention, the forming preferably comprises the following steps:
[0092] ① subjecting the composite carrier catalyst to first tableting, grinding and screening in sequence to obtain a first catalyst;
[0093] ② The first catalyst obtained in step ①, pseudo-boehmite, sesbania powder, PEG20000, solvent and peptizing agent are mixed and kneaded to obtain a second catalyst;
[0094] ③ The second catalyst obtained in step ② is sequentially air-dried, dried, calcined and tableted.
[0095] The present invention can further improve the activity of the catalyst by controlling the shaping operation.
[0096] In the present invention, the composite carrier catalyst is preferably subjected to first tableting, grinding and sieving in sequence to obtain the first catalyst.
[0097] The present invention has no particular limitation on the first tableting, grinding and screening operations, and operations well known to those skilled in the art may be used.
[0098] After obtaining the first catalyst, the present invention preferably mixes the first catalyst, pseudo-boehmite, sesbania powder, PEG20000, a solvent and a peptizing agent, and kneads them to obtain a second catalyst.
[0099] In the present invention, the solvent is preferably an inorganic solvent, more preferably deionized water. The present invention has no particular limitation on the amount of deionized water used, and it only needs to dissolve the raw materials.
[0100] In the present invention, the peptizing agent is preferably a nitric acid solution; the mass concentration of the nitric acid solution is preferably 10%; the ratio of the total mass of the first catalyst, pseudo-boehmite, sesbania powder and PEG20000 to the mass of the nitric acid solution is preferably (13-14):11, more preferably 13.8:11.
[0101] In the present invention, the mass ratio of the composite carrier catalyst, pseudo-boehmite, sesbania powder and PEG20000 is preferably (10-12): (3-5): (0.2-0.5): 0.5, and more preferably 10: 3: 0.3: 0.5.
[0102] The present invention has no special limitation on the operation of mixing the first catalyst, pseudo-boehmite, sesbania powder, PEG20000, solvent and peptizing agent, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.
[0103] The present invention has no particular limitation on the kneading operation, and any operation well known to those skilled in the art may be used.
[0104] After obtaining the second catalyst, the present invention preferably performs air-drying, drying, calcination and second tableting on the second catalyst in sequence.
[0105] The present invention has no particular limitation on the air-drying and drying operations, and operations well known to those skilled in the art may be used.
[0106] In the present invention, the calcination temperature is preferably 500-600° C., and the calcination time is preferably 1-3 hours.
[0107] The present invention has no special limitation on the operation of the second tabletting operation, and the operation well known to those skilled in the art can be adopted.
[0108] In another technical solution of the present invention, the forming is preferably tabletting. The present invention has no special limitation on the tabletting operation, and the operation well known to those skilled in the art can be adopted.
[0109] After the shaping is completed, the present invention preferably grinds and sieves the product obtained by shaping in sequence.
[0110] The present invention has no particular limitation on the grinding and screening operations, and operations well known to those skilled in the art may be used.
[0111] After obtaining the shaped catalyst, the present invention preferably uses the shaped catalyst to catalyze oxidation reaction of hydrogen chloride in an oxygen atmosphere to obtain chlorine.
[0112] In the present invention, the flow ratio of hydrogen chloride to oxygen is preferably 3:1 to 1:3; the temperature of the catalytic oxidation reaction is preferably 300 to 500°C, more preferably 360 to 400°C; the catalytic oxidation reaction is preferably carried out at normal pressure; the catalytic oxidation reaction is preferably carried out in a fixed bed reactor. The present invention has no special limitation on the model of the fixed bed reactor, and instruments and equipment familiar to those skilled in the art can be used.
[0113] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0114] Example 1
[0115] The preparation method of the composite supported catalyst comprises the following steps:
[0116] (1) 10 g of aluminum hydroxide, 10 g of sodium hydroxide and deionized water were mixed under stirring, reacted for 3 h under boiling conditions to obtain a sodium aluminate solution, and cooled to room temperature; then dilute nitric acid was added to adjust the pH value to 7.5, maintained at 50° C. for 0.5 h, and filtered while hot to obtain an aluminum hydroxide gel; dilute ammonia water was added to adjust the pH value to 8.0, stirred at 45° C. for 5 min after condensation, filtered and washed 3 times, then deionized water and 10 g of mesoporous Y-type molecular sieve NKF-7-4 were added, mixed thoroughly, and then allowed to stand at room temperature for 12 h, dried in an oven at 110° C. for 12 h, and finally calcined at 580° C. in an air atmosphere for 3 h to obtain a composite carrier; wherein the γ-Al 2 O 3 The mass content is 50%;
[0117] (2) 4.53 g of Cu(NO 3 ) 2 ·3H 2O was dissolved in 20 mL of deionized water, and after it was completely dissolved, 10 g of the composite carrier obtained in step (1) was added, and after being fully stirred, it was allowed to stand for 12 h, dried in an oven at 110 ° C for 12 h, and then ground, and then calcined at 580 ° C in an air atmosphere for 5 h to obtain a composite carrier catalyst.
[0118] Example 2
[0119] The preparation method of the composite supported catalyst comprises the following steps:
[0120] (1) 10 g of aluminum hydroxide, 10 g of sodium hydroxide and deionized water were mixed under stirring, reacted for 3 h under boiling conditions to obtain a sodium aluminate solution, and cooled to room temperature; then dilute nitric acid was added to adjust the pH value to 7.5, maintained at 50° C. for 0.5 h, and filtered while hot to obtain an aluminum hydroxide gel; dilute ammonia water was added to adjust the pH value to 8.0, stirred at 45° C. for 5 min after condensation, filtered and washed 3 times, then deionized water and 10 g of microporous Y-type molecular sieve XFF10 were added, mixed thoroughly, and then allowed to stand at room temperature for 12 h, dried in an oven at 110° C. for 12 h, and finally calcined at 580° C. in an air atmosphere for 3 h to obtain a composite carrier; wherein the γ-Al in the composite carrier 2 O 3 The mass content is 50%;
[0121] (2) 4.53 g of Cu(NO 3 ) 2 ·3H 2 O was dissolved in 20 mL of deionized water, and after it was completely dissolved, 10 g of the composite carrier obtained in step (1) was added, and after being fully stirred, it was allowed to stand for 12 h, dried in an oven at 110 ° C for 12 h, and then ground, and then calcined at 580 ° C in an air atmosphere for 5 h to obtain a composite carrier catalyst.
[0122] Example 3
[0123] The preparation method of the composite supported catalyst comprises the following steps:
[0124] (1) 10 g of aluminum hydroxide, 10 g of sodium hydroxide and deionized water were mixed under stirring, reacted for 3 h under boiling conditions to obtain a sodium aluminate solution, and cooled to room temperature; then dilute nitric acid was added to adjust the pH value to 7.5, maintained at 50° C. for 0.5 h, and filtered while hot to obtain an aluminum hydroxide gel; dilute ammonia water was added to adjust the pH value to 8.0, stirred at 45° C. for 5 min after condensation, filtered and washed 3 times, then deionized water and 10 g of mesoporous Y-type molecular sieve NKF-7-4 were added, mixed thoroughly, and then allowed to stand at room temperature for 12 h, dried in an oven at 110° C. for 12 h, and finally calcined at 580° C. in an air atmosphere for 3 h to obtain a composite carrier; wherein the γ-Al 2 O3 The mass content is 50%;
[0125] (2) 4.53 g of Cu(NO 3 ) 2 ·3H 2 O, 0.46 g Ce(NO 3 ) 3 6H 2 O was dissolved in 20 mL of deionized water, and after it was completely dissolved, 10 g of the composite carrier obtained in step (1) was added, and after being fully stirred, it was allowed to stand for 12 h, dried in an oven at 110 ° C for 12 h, and then ground, and then calcined at 580 ° C in an air atmosphere for 5 h to obtain a composite carrier catalyst.
[0126] Example 4
[0127] The preparation method of the composite supported catalyst comprises the following steps:
[0128] (1) 10 g of aluminum hydroxide, 10 g of sodium hydroxide and deionized water were mixed under stirring, reacted for 3 h under boiling conditions to obtain a sodium aluminate solution, and cooled to room temperature; then dilute nitric acid was added to adjust the pH value to 7.5, maintained at 50° C. for 0.5 h, and filtered while hot to obtain an aluminum hydroxide gel; dilute ammonia water was added to adjust the pH value to 8.0, stirred at 45° C. for 5 min after condensation, filtered and washed 3 times, then deionized water and 10 g of microporous Y-type molecular sieve XFF10 were added, mixed thoroughly, and then allowed to stand at room temperature for 12 h, dried in an oven at 110° C. for 12 h, and finally calcined at 580° C. in an air atmosphere for 3 h to obtain a composite carrier; wherein the γ-Al in the composite carrier 2 O 3 The mass content is 50%;
[0129] (2) 4.53 g of Cu(NO 3 ) 2 ·3H 2 O, 0.46 g Ce(NO 3 ) 3 6H 2 O was dissolved in 20 mL of deionized water, and after it was completely dissolved, 10 g of the composite carrier obtained in step (1) was added, and after being fully stirred, it was allowed to stand for 12 h, dried in an oven at 110 ° C for 12 h, and then ground, and then calcined at 580 ° C in an air atmosphere for 5 h to obtain a composite carrier catalyst.
[0130] Example 5
[0131] The preparation method of the composite supported catalyst comprises the following steps:
[0132] (1) 10 g of aluminum hydroxide, 10 g of sodium hydroxide and deionized water were mixed under stirring, reacted for 3 h under boiling conditions to obtain a sodium aluminate solution, and cooled to room temperature; then dilute nitric acid was added to adjust the pH value to 7.5, maintained at 50° C. for 0.5 h, and filtered while hot to obtain an aluminum hydroxide gel; dilute ammonia water was added to adjust the pH value to 8.0, stirred at 45° C. for 5 min after condensation, filtered and washed 3 times, and then deionized water and 5 g of microporous Y-type molecular sieve XFF10 and 5 g of mesoporous Y-type molecular sieve NKF-7-4 were added, mixed thoroughly, and then allowed to stand at room temperature for 12 h, dried in an oven at 110° C. for 12 h, and finally calcined at 580° C. in an air atmosphere for 3 h to obtain a composite carrier; wherein the γ-Al 2 O 3 The mass content is 50%;
[0133] (2) 4.53 g of Cu(NO 3 ) 2 ·3H 2 O, 0.46 g Ce(NO 3 ) 3 6H 2 O was dissolved in 20 mL of deionized water, and after it was completely dissolved, 10 g of the composite carrier obtained in step (1) was added, and after being fully stirred, it was allowed to stand for 12 h, dried in an oven at 110 ° C for 12 h, and then ground, and then calcined at 580 ° C in an air atmosphere for 5 h to obtain a composite carrier catalyst.
[0134] Comparative Example 1
[0135] 3.27 g of Cu(NO 3 ) 2 ·3H 2 O was completely dissolved in 20 mL of deionized water and 10 g of γ-Al 2 O 3 The catalyst was obtained by impregnation at room temperature for 12 h, drying in an oven at 110°C for 12 h, and calcining at 580°C in air atmosphere for 5 h.
[0136] Comparative Example 2
[0137] 3.27 g of Cu(NO 3 ) 2 ·3H 2 O was completely dissolved in 20 mL of deionized water, 10 g of mesoporous Y-type molecular sieve was added and immersed at room temperature for 12 h, dried in an oven at 110 °C for 12 h, and calcined at 580 °C in air atmosphere for 5 h to obtain a catalyst.
[0138] Comparative Example 3
[0139] 3.27 g of Cu(NO 3 )2 ·3H 2 O was completely dissolved in 20 mL of deionized water, 10 g of microporous Y-type molecular sieve was added and immersed at room temperature for 12 h, dried in an oven at 110 °C for 12 h, and calcined in an air atmosphere at 580 °C for 5 h to obtain a catalyst.
[0140] Application Examples 1 to 5 and Comparative Application Examples 1 to 3
[0141] 0.5 g of the composite supported catalysts prepared in Examples 1 to 5 and the catalysts prepared in Comparative Examples 1 to 3 were respectively tableted at 20 MPa, then ground and sieved to 20 to 40 mesh, and then loaded into a fixed bed reactor. The chlorine yield (i.e., hydrogen chloride conversion rate) after 8 h and 1000 h of reaction at normal pressure under the conditions of a hydrogen chloride flow rate of 32 mL / min, a reaction temperature of 400° C., and a hydrogen chloride to oxygen flow ratio of 1:2 is shown in Table 1 (the gas flowing out of the upper end of the reactor is passed into an acidic potassium iodide solution, and the amount of chlorine absorbed by the solution, i.e., the amount of chlorine generated by the reaction, is measured by iodine titration. The conversion rate of hydrogen chloride is then calculated to evaluate the performance of the catalyst).
[0142] Application Example 6
[0143] 10 g of the composite carrier catalyst prepared in Example 5 was weighed, pressed and ground, sieved to 120 mesh or more, 3 g of pseudo-boehmite, 0.3 g of sesbania powder and 0.5 g of PEG20000 were added to deionized water and mixed evenly, and 11 g of 10% dilute nitric acid, knead, then dry at room temperature, dry in an oven at 120℃ for 4h, put into a muffle furnace at 500℃ for 3h, then press into tablets at 20MPa, then grind, sieve to 20-40 mesh, and then load into a fixed bed reactor, under the conditions of hydrogen chloride flow rate of 32mL / min, reaction temperature of 420℃, hydrogen chloride to oxygen flow ratio of 1:2, react at normal pressure for 8h and 1000h. The chlorine yield (i.e., hydrogen chloride conversion rate) is shown in Table 1 (the gas flowing out of the upper end of the reactor is passed into an acidic potassium iodide solution, and the amount of chlorine absorbed by the solution, i.e., the amount of chlorine generated by the reaction, is measured by iodine titration. Then the conversion rate of hydrogen chloride is calculated to evaluate the performance of the catalyst).
[0144] Table 1 Hydrogen chloride conversion rate after catalysis for 8h and 1000h in Application Examples 1 to 6 and Comparative Application Examples 1 to 3
[0145]
[0146]
[0147] As can be seen from Table 1, compared with the comparative example, the composite supported catalyst of the embodiment of the present invention has excellent catalytic activity and long service life, and the conversion rate of preparing chlorine is further increased to 97.2%. This is the result of the synergistic catalytic effect of each component. The acidic center of the Y-type molecular sieve and the γ-Al 2 O 3 The combined effect of the acidic sites of the catalyst improves the activity and selectivity of the catalytic reaction. At the same time, the composite of the carrier can optimize the pore structure of the single carrier, improve the adsorption and diffusion properties of the catalyst, and facilitate the mass transfer and diffusion of the reactants inside the catalyst, thereby increasing the reaction rate and product yield. 2 O 3 Composited on the Y-type molecular sieve, the mechanical strength and thermal stability of the catalyst are improved. This enhanced stability can extend the service life of the catalyst and reduce production costs. By adding the promoter Ce, the activity and selectivity of the catalyst are further improved, and the catalytic reaction is promoted; the formed catalyst has better mechanical properties and thermal stability, which helps to improve the heat and mass transfer performance of the catalyst, thereby improving the reaction efficiency.
[0148] It can be seen from the above comparative examples and embodiments that the composite supported catalyst prepared by the preparation method provided by the present invention has high activity and high stability.
[0149] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a composite supported catalyst comprises the following steps: (1) mixing aluminum hydroxide, Y-type molecular sieve and a first solvent, aging the mixed product, and then sequentially drying and first calcining to obtain a composite carrier; (2) mixing the composite support obtained in step (1), a divalent copper salt and a second solvent for loading, and drying and grinding the loaded product to obtain a support loaded with a precursor; trivalent cerium salt is also added in step (2); (3) subjecting the carrier loaded with the precursor obtained in step (2) to a second calcination to obtain a composite carrier catalyst; The Y-type molecular sieve in step (1) is a mesoporous Y-type molecular sieve and a microporous Y-type molecular sieve.
2. The preparation method according to claim 1, characterized in that: The temperature of the first calcination in the step (1) is 480-580° C., and the time of the first calcination is 3-4 hours.
3. The preparation method according to claim 1, characterized in that: In the step (1), the mass content of γ-Al2O3 in the composite carrier is 50-90%.
4. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the divalent copper salt to the composite carrier is (0.4-0.5):
1.
5. The preparation method according to claim 1, characterized in that: The loading temperature in step (2) is room temperature, and the loading time is 10 to 12 hours.
6. The preparation method according to claim 1, characterized in that: The temperature of the second roasting in step (3) is 430-580° C., and the time of the second roasting is 4-5 hours.
7. The composite supported catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the composite supported catalyst according to claim 7 in the catalytic oxidation of hydrogen chloride to produce chlorine.
Citation Information
Patent Citations
Catalyst for preparing chlorine gas through catalytic oxidation of hydrogen chloride as well as preparation method and application of catalyst
CN114713250A
Catalyst for preparing chlorine gas through catalytic oxidation of hydrogen chloride as well as preparation method and application of catalyst
CN118106020A